Newborn Health Interventions and Challenges for Implementation in Nepal - Khatri, Resham Bahadur; Mishra, Shiva Raj; Khanal, Vishnu; Gelal, Khageshwor; Neupane, Subas (Frontiers in Public Health, 2016)
Neonatal mortality is a major challenge in reducing child mortality rates in Nepal. Despite efforts by the Government of Nepal, data from the last three demographic and health surveys show a rise in the contribution of neonatal deaths to infant and child mortality. The Government of Nepal has implemented community-based programs that were piloted and then scaled up based on lessons learned. These programs include, but are not limited to ensuring safe motherhood, birth preparedness package, community-based newborn care package, and integrated management of childhood illnesses. Despite the implementation of such programs on a larger scale, their effective coverage is yet to be achieved. Health system challenges included an inadequate policy environment, funding gaps, inadequate procurement, and insufficient supplies of commodities, while human resource management has been found to be impeding service delivery. Such bottlenecks at policy, institutional and service delivery level need to be addressed incorporating health information in decision-making as well as working in partnership with communities to facilitate the utilization of available services.